Diagnosis and Management of Cardioembolic Stroke. Issue 2 (April 2023) - Yaghi, Shadi
ABSTRACT: OBJECTIVE: Cardioembolic stroke accounts for nearly 30% of ischemic strokes. Prompt diagnosis of the underlying mechanism may improve secondary prevention strategies. This article reviews recent randomized trials, observational studies, case reports, and guidelines on the diagnosis and treatment of cardioembolic stroke. LATEST DEVELOPMENTS: Several pathologies can lead to cardioembolic stroke, including atrial fibrillation, aortic arch atheroma, patent foramen ovale, left ventricular dysfunction, and many others. Secondary stroke prevention strategies differ across these heterogeneous mechanisms. In addition to medical treatment advances such as the use of direct oral anticoagulants in patients with atrial fibrillation, surgical treatments such as closure of patent foramen ovale have been shown to reduce the risk of recurrent stroke in select patients. Furthermore, left atrial appendage occlusion is a promising strategy for patients with atrial fibrillation who are candidates for short-term oral anticoagulation therapy but not long-term oral anticoagulation therapy. ESSENTIAL POINTS: A thorough diagnostic evaluation is essential to determine cardioembolic causes of stroke. In addition to risk factor management and lifestyle modifications, identification and targeting of the underlying cardioembolic stroke mechanisms will lead to improved stroke prevention strategies in patients with cardioembolic stroke.